FORCES ACTING ON CLASS-5 RESTORATIONS - P.A. , Vasishta; Somasundaram, Jayalakshmi; Sivaswamy, Vinay (International Journal of Psychosocial Rehabilitation, 2020)
The main aim of the review is to discuss the forces acting on the class 5 restoration. A thorough literature search was performed using databases like PubMed, Google Scholar, BioRxiv, MESH, and the Cochrane database using the keywords ‘forces, ‘class 5,’ and ‘restoration’ with no date and year restrictions. The language is restricted to English. 8 articles with similar data were found, which were analyzed and have been included in this study. The effect of brushing in class 5 restoration leads to poor esthetics, and the person loses the confidence to smile. Vigorous and improper brushing damages the class 5 restoration. Class 5 cavities involve caries affecting the gingival one-third of facial or lingual surfaces of anterior or posterior teeth. Class 5 has only one surface, and there is no direct force acting on it, so it is free of mechanical problems. A tooth can withstand force because of the resiliency of dentin. Several studies have demonstrated that the use of an adhesive matrix decreases cuspal flexure compared with occlusal amalgam restoration. The depth of an occlusal restoration, particularly, is more critical than the width. Some instances also showed that the peak stresses were greater than the known bond strengths of composite to dentine.